2006
DOI: 10.1111/j.1471-4159.2006.04051.x
|View full text |Cite
|
Sign up to set email alerts
|

JAK2 and STAT3 activation contributes to neuronal damage following transient focal cerebral ischemia

Abstract: Increased levels of interleukin-6 (IL-6) play a role in post-ischemic cerebral inflammation. IL-6 binding to its receptors induces phosphorylation of the receptor associated janus kinases (JAKs), and the down-stream signal transducer and activator of transcription (STAT) family of transcription factors, which amplify the IL-6 signal transduction. We evaluated the functional significance of JAK2 and STAT3 activation in focal ischemia-induced neuronal damage. Transient middle cerebral artery occlusion in adult r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
171
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(183 citation statements)
references
References 51 publications
10
171
1
1
Order By: Relevance
“…NFB2 gene encodes NFB2 p100/p52 protein, which exhibits IB properties due to a cluster of ankyrin repeats in the C-terminal domains. NFB2 p100 mediates cytoplasmic retention of NFB RelA/p65 to prevent its nuclear translocation, and thus minimizes inflammation and cell death after ischemia (Schneider et al, 1999;Zhang et al, 2005). Hence, RESTmediated repression of NFB2 might be a promoter of neuronal death after ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NFB2 gene encodes NFB2 p100/p52 protein, which exhibits IB properties due to a cluster of ankyrin repeats in the C-terminal domains. NFB2 p100 mediates cytoplasmic retention of NFB RelA/p65 to prevent its nuclear translocation, and thus minimizes inflammation and cell death after ischemia (Schneider et al, 1999;Zhang et al, 2005). Hence, RESTmediated repression of NFB2 might be a promoter of neuronal death after ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…ously (Satriotomo et al, 2006;Pandi et al, 2013). In brief, siRNA mix (8 nmol in 6 l buffer ϩ 2 l invivofectamine) was incubated at room temperature for 15 min and injected with a Hamilton syringe (1 l/5 min) into cerebral cortex (bregma; Ϫ0.2 mm posterior, 3 mm dorsoventral, 4.5 mm lateral) (Paxinos and Watson, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…A novel mechanism for the PPAR-gamma-independent anti-inflammatory actions of TZDs, is the involvement of the Janus kinase (JAK) and the STAT signaling pathways (33,67,68). Transphosphorylation of the cytokine receptor-associated JAK leads to its dimerization and phosphorylation of the downstream STATs.…”
Section: Ppar-gamma-independent-mechanismsmentioning
confidence: 99%
“…SOCS acts as a negative feedback regulator and inhibits further JAK and STAT phosphorylation, thus preventing the upregulation and binding of cytokines to their receptors after an acute CNS insult (33,67). Our recent studies showed that focal ischemia induces a massive upregulation of IL-6, which increases the phosphorylation of the JAK2 and STAT3 isoforms in the ischemic hemisphere (68,69,123). Although physiological levels of STAT3 activation are essential for normal cellular functions, its excessive phosphorylation as seen after focal cerebral ischemia is neurotoxic.…”
mentioning
confidence: 99%
See 1 more Smart Citation